Estrategias de aprovechamiento de productos forestales no maderables como indicador de enfoque ABE en la comunidad Mocochal, Bolívar-Manabí-Ecuador - Muñoz Loor, Dayanna Andreina (2023)
The research focused on establishing strategies for the sustainable use of non-timber forest products (NTFP) as an EbA approach indicator in the Mocochal community, Bolívar canton, province of Manabí. The approach was quantitative, non-experimental. Four plots were designed to inventory species and calculate their importance. Additionally, focus groups will be consulted to determine the use of NTFPs. The species with the highest number of uses include guasmo with 9%, Beldaco with 7%, and Guachapelí, Mate and Mango, each with 6%. On the other hand, the Guarumo, the Laurel, the Mouse Yuca, the Arrayán, the Achiote and the Laurel prieto had 4% each. Overall, the results indicated high diversity. Furthermore, the forms of use of NTFPs have been distributed as follows: 20% for use in human medicine, another 20% in construction materials and farming tools, 14% used in food and beverages, 11 % destined for the creation of crafts, 10% for the extraction of essential oils, 4% for fodder, another 4% for mystical and ritual applications, 3% for toxic fines, another 3% for fibers, 1% destined to colorants and dyes, and another 1% for ornamental uses. With the information collected, a good practice guide for the sustainable use of identified NTFPs was developed, which includes a total of 13 EbA measures designed to preserve and use these resources appropriately.